Sero-prevalence of Helicobacter pylori Infection in Neyshabur, Iran, During 2010-2015 - Mohammad Salehi; Abdolmajid Ghasemian; Seyyed Khalil Shokouhi Mostafavi; Somayyeh Najafi; Hassan Rajabi Vardanjani (Iranian Society of Pathology, 2017)
Backgrounds & Objective: The Helicobacter pylori prevalence has continuously decreased during recent years in Iran. The current study aimed at determining H. pylori prevalence in Neyshabur city, Northeast Iran, during 2010-2015. Methods: The current epidemiologic survey was conducted in Neyshabur from 2010 to 2015 to determine the prevalence of H. pylori infection. A total of 11596 participants (3681 male with the mean age of 31.7±6.2 years and 7915 female with mean age of 68.3±4.7 years) were included. The enzyme-linked immunosorbent assay kits for the detection of H. pylori and Stat Fax 3200® Microplate Reader (USA) with a sensitivity of 95% and specificity of 98% were used. Titers above 12 units were considered positive for IgG, IgA, and IgM (negative <8, equivocal 8 to 12, and positive >12 U). The Chi-square t test and F test were used to analyze data. Results: The overall IgA, IgG, and IgM seropositive samples among the study participants were 852 (7.2%),         9000 (72.8%), and 1256 (5.2%), respectively. The IgA seropositivity was significantly high among the age group above 51 years, compared with the other age groups. Moreover, the IgG and IgM seropositivity were significantly high among the age groups 41 to 50 and 31 to 40 years respectively, compared with the other age groups. There was no significant difference between male and female cases regarding IgA and IgG seropositive samples, but IgM level was significantly higher among females, compared with that of the male cases. Furthermore, there was no significant alteration in IgA, IgG, and IgM seropositivity during 2010-2014 in Neyshabur. Conclusion: The prevalence of H. pylori in Neyshabur was high in the healthy population. Furthermore, the H. pylori prevalence did not change from 2010 to 2014 in the studied city. Effective approaches to improve health, educational, and socioeconomic status should be implemented to minimize and control H. pylori infection.